1996
DOI: 10.1074/jbc.271.15.9024
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte Nuclear Factor-4 Is Responsible for the Liver-specific Expression of the Gene Coding for Hepatocyte Growth Factor-like Protein

Abstract: In an attempt to understand the molecular mechanism regulating the expression of the gene coding for human hepatocyte growth factor-like protein/macrophage stimulating protein (HGFL), our laboratory has isolated and characterized approximately 4200 bp of the 5-flanking region of the HGFL gene. To determine the location of sites which may be critical for the function of the HGFL gene promoter, we constructed a series of hybrid genes containing serial deletions of this region attached to the coding sequences for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 34 publications
3
5
0
Order By: Relevance
“…To determine whether SF-Ron contributes to this HGFL/Ronmediated morphological response, peritoneal macrophages isolated from wild-type mice and mice heterozygous (ϩ/FL) or homozygous (FL/FL) for the FL-Ron allele were analyzed for HGFL-induced morphological shape changes indicative of activation. Macrophages from wild-type mice had similar baseline levels of activated macrophages and in response to HGFL underwent morphological shape changes to a degree consistent with published analyses (data not shown) (2,18,27,28). Interestingly, both ϩ/FL and homozygous FL/FL macrophages responded to HGFL to the same degree as macrophages isolated from wild-type mice.…”
Section: Analysis Of Alternative Ron Receptor Mrna Expression In Fl-rsupporting
confidence: 84%
See 1 more Smart Citation
“…To determine whether SF-Ron contributes to this HGFL/Ronmediated morphological response, peritoneal macrophages isolated from wild-type mice and mice heterozygous (ϩ/FL) or homozygous (FL/FL) for the FL-Ron allele were analyzed for HGFL-induced morphological shape changes indicative of activation. Macrophages from wild-type mice had similar baseline levels of activated macrophages and in response to HGFL underwent morphological shape changes to a degree consistent with published analyses (data not shown) (2,18,27,28). Interestingly, both ϩ/FL and homozygous FL/FL macrophages responded to HGFL to the same degree as macrophages isolated from wild-type mice.…”
Section: Analysis Of Alternative Ron Receptor Mrna Expression In Fl-rsupporting
confidence: 84%
“…Peritoneal macrophages show dramatic morphological changes in response to HGFL in vitro (10,18,24,27,28,31,32). To determine whether SF-Ron contributes to this HGFL/Ronmediated morphological response, peritoneal macrophages isolated from wild-type mice and mice heterozygous (ϩ/FL) or homozygous (FL/FL) for the FL-Ron allele were analyzed for HGFL-induced morphological shape changes indicative of activation.…”
Section: Analysis Of Alternative Ron Receptor Mrna Expression In Fl-rmentioning
confidence: 99%
“…Promoter analyses have suggested that the transcription factor hepatocyte nuclear factor-4 is important for the liver-specific expression of HGFL (Waltz et al, 1996). Specific elements in the first intron of HGFL have also been found to regulate liver-and kidney-specific expression (Wetzel et al, 2003).…”
Section: Ron Ligand Structure and Functionmentioning
confidence: 99%
“…Transfections were performed using the calcium-phosphate precipitation method as previously described (Waltz et al, 1996). Cells were maintained in Dulbecco's Modi®ed Eagle's Medium (DMEM, Gibco) supplemented with 10% fetal calf serum, 2 mM 1-glutamine, and 50 ug/ml gentamicin (Gibco).…”
Section: Cell Culture Transfection and Rna Analysismentioning
confidence: 99%